2020
DOI: 10.1371/journal.pone.0233815
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive effect of an inward rectifier K+ channel blocker peptide, tertiapin-RQ

Abstract: Renal outer medullary K+ channel, ROMK (Kir1.1, kcnj1) is expressed in the kidney and brain, but its role in the central nervous system remains unknown. Recent studies suggested an involvement of the ROMK channel in mental diseases. Tertiapin (TPN) is a European honey bee venom peptide and is reported to selectively block the ROMK channel. Here, we have chemically synthesized a series of mutated TPN peptides, including TPN-I8R and -M13Q (TPN-RQ), reported previously, and examined their blocking activity on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(78 reference statements)
0
5
0
Order By: Relevance
“…That study found that these effects involve the suppression of neural activities in a different nucleus, the lateral septum. In addition, we also demonstrated that the suppression of this nucleus is also involved in the antidepressive effect of ROMK (Kir1.1) channel blocker, tertiapin-RQ ( Okada et al, 2020 ). Thus, K⁺ channel modulators, e.g., ostruthin, are promising as antidepressants and should be further investigated for clinical application.…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…That study found that these effects involve the suppression of neural activities in a different nucleus, the lateral septum. In addition, we also demonstrated that the suppression of this nucleus is also involved in the antidepressive effect of ROMK (Kir1.1) channel blocker, tertiapin-RQ ( Okada et al, 2020 ). Thus, K⁺ channel modulators, e.g., ostruthin, are promising as antidepressants and should be further investigated for clinical application.…”
Section: Introductionmentioning
confidence: 67%
“…After tests on the 6th day, mice were subjected to SPT for 24 hrs, and sucrose solution/water consumption and food intake were measured. Each behavioral test was performed according to a method reported previously ( Joseph et al, 2018 , Okada et al, 2020 )…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Enhanced propionyl carnitine is regarded as a biomarker of vitamin B-12 deficiency. Ostruthin has its role in anxiety and depression control which are common mental disorders ( Okada et al, 2020 ). Resorcinol is used in cosmetic pharmaceutical products as an anti-septic and infectant removal for the cure of skin problems and infections such as acne, seborrheic dermatitis, eczema, psoriasis, corns, calluses, and warts ( Fabri et al, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4] Because reduction of the grain boundary energy also increases the grain boundary strength, improved fatigue and impact strengths of structural steels by doping B have been reported because of grain boundary crack suppression. [5][6][7] Improvement of hardenability by doping B varies along with materials' production conditions and alloy compositions. Earlier reports have described that segregation of B on γ grain boundaries is influenced strongly by metallurgical phenomena in hot deformation: recrystallization generating new grain boundaries, diffusion of B to segregate on the newly generated grain boundaries, and formation of M 23 (C,B) 6 precipitates on the grain boundaries.…”
Section: Introductionmentioning
confidence: 99%